Survey of European and Major ISC Facilities for Supporting Mars and Sample Return Mission Aerothermodynamics and Tests Required for Thermal Protection System and Dynamic Stability. (19th June 2011) - Bugel, Mathilde; Reynier, Philippe; Smith, Arthur
Abstract : In the frame of future sample return missions to Mars, asteroids, and comets, investigated by the European Space Agency, a review of the actual aerodynamics and aerothermodynamics capabilities in Europe for Mars entry of large vehicles and high-speed Earth reentry of sample return capsule has been undertaken. Additionally, capabilities in Canada and Australia for the assessment of dynamic stability, as well as major facilities for hypersonic flows available in ISC, have been included. This paper provides an overview of European current capabilities for aerothermodynamics and testing of thermal protection systems. This assessment has allowed the identification of the needs in new facilities or upgrade of existing ground tests for covering experimentally Mars entries and Earth high-speed reentries as far as aerodynamics, aerothermodynamics, and thermal protection system testing are concerned.